LITERARY INTERPRETATION OF SOCIAL PSYCHOLOGY IN THE NOVEL “MARTIN EDEN” - Aralova Lobar (TADQIQOTLAR, 2025)
Abstract: Literary interpretation of social psychology in the novel “Martin Eden” is analyzed in the article.